Self-Assessed Gap of Acquired and Desired Assessment Skills of Prospective Teachers - Muhammad Sarwar, Muhammad Perveiz, Mubashar Nadeem, (PJE, 2023)
The difference between the skills desired to carry out assessments tasks and t he s kills a ctually a cquired du ring p re-service t eaching t raining program by prospective teachers is being referred to as skills’ gap. The study dr aws i ts ba sis from 5 th national professional s tandards f or teachers, which describes necessary assessment skills for teachers. This study i ntends to f ind out t he a ssessment sk ills of p rospective teachers. The as sessment sk ills co nsisting of 39 items and three subscales w ere used t o collect da ta f rom 333 pr ospective t eachers s elected f rom f our public sector universities of central P unjab.